Desempenho de um sistema de drenagem subterrânea e análise econômico-social da produção de coco em solo recuperado da degradação por sais - Quispe, Magaly Condori (2024)
One of the techniques developed for the recovery and incorporation of waterlogged, saline and sodic soils is the implementation of underground drainage systems and supplementary irrigation to improve soil quality in order to improve production conditions. In this context, this research aimed to evaluate the hydraulic performance of an underground drainage system as well as the attributes of water transmission in the soil, soil chemical attributes and profitability in the cultivation of dwarf coconut palms in a family farmer's area that has been subjected to a saline-sodic soil recovery process for 13 years, in the Curu Irrigation Project - Pentecoste, Ceará. The underground drainage system was evaluated by means of hydraulic performance in the transmission of water in the soil, as well as the physical-chemical attributes of the soil, the quality of the irrigation water and the profitability of the green dwarf coconut tree in the 2023 agricultural year. The hydraulic performance of the underground drainage system consisted of analyzing the variables of the water table flow network, water table profiles between drain lines and comparative analysis between actual field spacing and spacing estimated by drainage equations in a non-permanent flow regime. Water transmission in the soil was assessed by means of hydraulic conductivity tests on saturated soil under field conditions and on soil samples in the laboratory. The electrical conductivity of the soil in the 1:2 extract (EC) and the percentage of exchangeable sodium (PST) were evaluated. In the economic and social dimensions, the social sustainability indicators added value and the economic sustainability indicator farmer's income were analyzed, which assesses the economic viability of the production system. The results of the survey led to the following conclusions: a) The groundwater flow network shows the central region of the area with the highest total potential values and therefore acts as a groundwater divider, whose flow lines run approximately perpendicular to the direction of the lateral drains with hydraulic gradients that signal the underground drainage system functions as an interception type; b) The water table lowering profiles reflect the low water transmission capacity of the soil, as reflected in the average value of the hydraulic conductivity of saturated soil (Ko) obtained in field tests; c) The value of the basic infiltration rate of the soil confirms that it should not be used instead of the value of the hydraulic conductivity of the saturated soil (Ko), as it would overestimate the value of the spacing between drains; d) The soil penetration resistance values at the depths evaluated show that they do not compromise the development of the coconut root system, and are consistent with the hydraulic resistance values, which show that there are no physical impediments; e) The analysis of the need for enclosures in the research area recommends the use of granular envelopes with zero-zero gravel or alternatively zero-zero gravel, instead of geotextile blankets, which could present a risk of clogging; f) The chemical attributes of the soil show that after the recovery process of the saline-sodic soil, the levels of salinity and sodicity are practically unchanged, and the soil is now at the sodic threshold, just as it was 13 years ago; g) The water source used for irrigation comes from the alluvial aquifer and poses no risk to the soil or the coconut crop, with the underground drainage system being vital in removing salts; h) The 0.4 ha pilot area allows the irrigating farmer to reach the level of social reproduction, which is only possible due to financing and the lack of intermediaries in the commercialization process.